2002
DOI: 10.1111/j.1651-2227.2002.tb01638.x
|View full text |Cite
|
Sign up to set email alerts
|

Faecal calprotectin levels in infants with infantile colic, healthy infants, children with inflammatory bowel disease, children with recurrent abdominal pain and healthy children

Abstract: Olafsdottir E, Aksnes L, Fluge G, Berstad A. Faecal calprotectin levels in infants with infantile colic, healthy infants, children with in ammatory bowel disease, children with recurrent abdominal pain and healthy children. Acta Paediatr 2002; 91: 45-50. Stockholm. ISSN 0803-5253 This study investigated faecal calprotectin concentration, a measure of intestinal in ammation, in infants and children with abdominal pain. Faecal calprotectin was measured by an enzyme-linked immunosorbent assay kit in spot stool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 32 publications
12
99
1
3
Order By: Relevance
“…The patients’ final diagnoses were extracted from the hospital charts. Patients were excluded when there was insufficient clinical information on the final diagnosis or if they were younger than 2 years of age, because particularly infants are known to have high FC levels in the absence of disease 16 17. In patients with proven IBD the disease activity at the time of stool sampling was judged by a paediatric gastroenterologist as clinical remission or active disease based on clinical history and physical examination.…”
Section: Methodsmentioning
confidence: 99%
“…The patients’ final diagnoses were extracted from the hospital charts. Patients were excluded when there was insufficient clinical information on the final diagnosis or if they were younger than 2 years of age, because particularly infants are known to have high FC levels in the absence of disease 16 17. In patients with proven IBD the disease activity at the time of stool sampling was judged by a paediatric gastroenterologist as clinical remission or active disease based on clinical history and physical examination.…”
Section: Methodsmentioning
confidence: 99%
“…As a general rule, markers expressed by phagocytes are more specific for inflammation, while markers also inducible in epithelial cells are more sensitive but can, on the other hand, increase in conditions of non-inflammatory stress, such as lactose intolerance 20. In addition, infants and small children can differ in their expression level of epithelial proteins, which appears at least partially related to feeding formula and the establishment of the normal gut flora 2123…”
Section: Faecal Biomarkers Of Mucosal Damagementioning
confidence: 99%
“…7 One study has suggested that infants with colic may have increased faecal calprotectin levels, 8 suggesting a possible role for gut inflammation; however, another study suggested no differences in faecal calprotectin levels between infants with and infants without colic. 9 No single effective treatment for colic exists, and most clinical guidelines recommend support and reassurance as the mainstay of management. [10][11][12][13] The use of hypoallergenic formulas or elimination of cow's milk protein from the diet of mothers who are breast feeding may possibly be effective, [10][11][12] yet not all irritable infants respond.…”
Section: Introductionmentioning
confidence: 99%